FATTY ACID COMPOSITION ANALYSIS OF OIL EXTRACT MICROALGAE Spirulina sp. WITH DIFFERENT EXTRACTION METHODS - Heder Djamaludin; Anies Chamidah (JFMR (Journal of Fisheries and Marine Research), 2021)
The microalgae Spirulina sp. is a potential biological resource. Utilization of Spirulina sp. very broad in various industrial fields such as nutraceutical, food, cosmetic and pharmaceutical. The purpose of this study was to analyze the chemical composition and fatty acid profile of the Spirulina sp. extracted by different mechanical cell disruption methods. This research method is descriptive, where the microalgae Spirulina sp. extracted using Microwave-Assisted Extraction (MAE) and Ultrasonic Assisted Extraction (UAE) methods, then the oil extract was analyzed for chemical composition and fatty acid profile with GC-MS instrument. The results showed that the oil extract of Spirulina sp. which extracted by MAE method contains 12 types of fatty acids where the levels of Saturated Fatty Acid are 56.01%, Mono-Unsaturated Fatty Acid 7.67%, and Poly-Unsaturated Fatty Acid 36.32%. Spirulina sp. oil extract contains ω-6 (17.17-18.87%) and ω-9 (4.34%) unsaturated fatty acids. Then the Spirulina sp. oil extract extracted by the UAE method contains 19 types of fatty acids where the levels of Saturated Fatty acids are 59.25%, Mono-Unsaturated Fatty acids 8.89%, and Poly-Unsaturated Fatty acids 40.87%. Spirulina sp. oil extract contains types of unsaturated fatty acids ω-3 (0.18-0.41%), ω-6 (18.39-27.73%), and ω-9 (3.50%). The highest fatty acid content in Spirulina sp. oil extract are palmitic acid/SFA (53.30-56.57%), oleic acid/MUFA (4.34-4.50%), and linoleic acid/PUFA (18.39-18.88%).